Sadako and the thousand paper cranes - Coerr, Eleanor (New York : Scholastic, 2000)
Hospitalized with the dreaded atom bomb disease, leukemia, a child in Hiroshima races against time to fold one thousand paper cranes to verify the legend that by doing so a sick person will become healthy.
Originally published: New York : Putnam, 1977.
Keywords: Sasaki, Sadako, 1943-1955 -- Juvenile literature